Optically Active Nanomaterials for Bioimaging and Targeted Therapy - Yang, Yu; Wang, Li; Wan, Bin; Gu, Yuxin; Li, Xinxin (Frontiers in Bioengineering and Biotechnology, 2019)
Non-invasive tracking for monitoring of the selective delivery and transplantation of biotargeted agents in vivo has been employed as one of the most effective tools in the nanomedicine field. Different nanoprobes have been developed and applied to bioimaging of tissues and treatment of some diseases ranging from inflammatory and cardiovascular diseases to cancer. Herein, we will review the recent advances in the development of optics-responsive nanomaterials including organic and inorganic nanoparticles for multimodal bioimaging and targeted therapy. Main focus is placed on the nanoprobe fabrication, mechanistic illustrations, and diagnostic or therapeutical applications. These nanomedicine strategies have promoted better understanding of biological events underlying diverse disease etiologies, thereby facilitating diagnosis, illness evaluation, therapeutic effect and drug discovery.